Innovation of the Campbell Vision Stimulator with the Use of Tablets - Brožek, Josef; Jakeš, Martin; Svoboda, Václav (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The article covers three fundamental themes: a) performance solutions using gaming to treat multiple eye defects; in particular - Amblyopia; b) an explanation of the issue and design of the software (including games) which is intended for therapeutic or health purposes; and c) highlighting the modern solutions and the power of software products for the needs of the health sector, in particular in the fields of diagnostics and rehabilitation. The reader can learn basic information about eye diseases and the principles of their treatment, and become acquainted with the reasons why computer games (and in particular video games) are appropriate for rehabilitation. Very important and beneficial for the reader is the section of the article which focuses on a) the differences in the design of standard software and software designed for the needs of the healthcare system, b) the high risks associated with defects of all software, or even the risk of side effects with the so-called „perfect“ software, c) the fact that a major part of software development does not comply with all of the standards. The article also discusses the advantages of the software solution over other methods of rehabilitation. Most of the paradigms are generally applicable. Familiarity with the principles of this application can thus be interesting even for developers in the relevant areas.
Inovace Campbellova zrakového stimulátoru za použití tabletu
Keywords: Innovation; Campbell; Vision; Stimulator; with; the; Use; Tablets; Inovace; Campbellova; zrakového; stimulátoru; použití; tabletu